On Prophetic Decolonization During the Roman Empire - Imam Nawawi (Journal of Islamic History and Manuscript, 2025)
This study examines the decolonization in the prophetic period of Muhammad SAW. Different analyses occur among historians, with some viewing Islam as supportive of colonialism and others as anti-colonialism. This study aims to answer how decolonization was practiced in the prophetic period. The study’s objective is to demonstrate that Prophet Muhammad SAW laid out the foundations of thoughts and actions of decolonization. The colonial enterprises undertaken during the subsequent caliphates, which some historians such as Philip K. Hitt assumed, differ fundamentally from the principles of governance in the prophetic era. This study employs a qualitative historical approach, utilizing the discourse analysis method to prove that the wars against the Eastern Romans waged by the Prophet Muhammad were for decolonization. The existing historical sources are collected from literary studies and then subjected to Michael Onyebuchi Eze’s theory, which asserts decolonization as an idea and practice transcending history. The study’s findings are as follows: (1) Roman colonialism in the Arabian Peninsula led to protracted conflicts between Arab tribes and transformed it into a theatre of proxy warfare against the Persian empire; (2) Prophet Muhammad SAW was a pivotal figure in decolonizing Roman influences on Arab(s). Prophet paved two primary steps, which were to unify the Arabs and to wrest control of the Arabian peninsula from Eastern Rome; and (3) the military campaigns led either directly or indirectly by Muhammad SAW were indisputable evidence of the prophetic practice and thought of decolonization.